Variable levels of antibiosis and/or antixenosis of Bt and non-Bt maize genotypes on Dalbulus maidis (Hemiptera: Cicadellidae) - Faria, Rodrigo D. [UNESP]; Baldin, Edson L. L. [UNESP]; Takaku, Vinicius S. [UNESP]; Canassa, Vinicius F. [UNESP] (Springer, 2021)
The corn leafhopper Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) poses a serious threat to the crop, causing direct and indirect damage to plants. The present study aimed to investigate the possible expression of resistance by antixenosis and/or antibiosis against D. maidis in 11 corn genotypes [8 non-Bt (60XB14, 90XB06, XB 9003, XB 8018, XB 8010, IAC 8390, IAC 8046, and IAC AIRAN) and 3 Bt (XB 7116 Bt, XB 8010 Bt, and DKB 310 Bt)] previously selected in a greenhouse. Initially, no choice preference tests for oviposition were performed to characterize the expression of antixenosis. To characterize the expression of antibiosis/antixenosis, the insects were confined to leaves of different genotypes to assess the following parameters: duration of each nymphal stage, nymphal period, viability per instar, total viability, and adult longevity. Additionally, morphological and physical analyses of the genotypes were carried out to establish correlations with the resistance categories. The genotypes 90XB06, IAC 8390, XB 9003 and DKB 310 PRO3 expressed antixenosis against leafhoppers, reducing insect oviposition. The genotypes 60XB14, 90XB06, IAC 8046, XB 8018 and IAC 8390 expressed antibiosis and/or antixenosis against leafhoppers, reducing nymphal viability. The hardness of the ribs is probably associated with the resistance of some of the evaluated genotypes and is an important morphological defense against leafhoppers. The results of this study are novel and can aid in corn-breeding programs focused on plant resistance to sucking insects, with relevant impacts on the integrated pest management of the crop.
Keywords: Zea mays L; Plant and insect resistance; Resistance factors; IPM